THE SPIDERS (ARACHNIDA, ARANEI) IN THE LANDSCAPE RESERVE "YAKHNIVSKY" (KIEV REGION) - GRYNYK, E.; SINGAYEVSKIY, Е. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
For the first time, the species composition and relative abundance of spiders in pine and alder forests within the Yakhnovsky reserve have been studied; 46 species of spiders which represent 17 families were found. It was found that quantitatively in the pine forest spiders of the families Linyphiidae (43,4 %) and Araneidae (42,9 %) prevail, and in the alder forest – Tetragnathidae (37 %) and Linyphiidae (34 %). In the herbaceous layer of the pine forest, spiders of Araneidae family dominated quantitatively, and in the litter dominated Linyphiidae spiders – 91 %. In the herbaceous layer of the alder forest Tetragnathidae spiders quantitatively dominated – 34 %, and in the litter layer Linyphiidae and Tetragnathidae, are dominants – respectively, 32 % and 43 %. The dominant species for the grass and litter layers were revealed (according to the Tischler scale): in the pine forest, these are Mangora acalypha (48,6 %), Linyphia triangularis (18,85 %) and Leptothrix hardyi (89 %); in the alder forest – Linyphia triangularis (24,1 %), Metellina segmentata (23 %), Tetragnatha pinicola (18,8 %) and Piratula hygrophila (38,5 %) with Pachygnatha listeri (19,2 %), in accordance with indicated tiers. Nine species of spiders were identified, of which five species – Agroeca cuprea (family Liocranidae), Bathyphantes nigrinus, Dicymbium nigrum, Floronia bucculenta and Neriene montana (family Linyphiidae), are indicated for the first time for the territory of Kiev Polesie, and four species, for the first time for Ukrainian Polesie: Cheiracanthuim elegans (family Cheiracanthiidae), Leptothrix hardyi, Sintula spiniger and Walckenaeria alticeps (family Linyphiidae). For these species is given the data on faunal material, places and methods of collection, distribution and ecological features. According to our own research and literary sources, the territory of Kiev Polesie currently includes 150 species of spiders. The indices of faunistic similarity and species diversity of the surveyed biotopes were calculated, an arealogical analysis was performed.
Keywords: spiders, fauna, species diversity, finds of new species, Kiev region, Kiev Polesie, "Yakhnivsky" landscape reserve